The effectiveness of a collage art training program in developing artistic creativity in designing educational tools for kindergarten teachers. (Al-Academy, 2025)
The current research aims to identify the effectiveness of a collage training program in developing artistic creativity in designing educational materials for kindergarten teachers. To achieve the research objectives, the following hypotheses were formulated:The researcher concluded that the program used was effective in developing the artistic creativity of kindergarten teachers in preparing educational materials for the experimental group. The program contributed significantly to increasing the artistic creativity of kindergarten teachers, while no statistically significant change occurred in the artistic creativity of kindergarten teachers in the control group.The researcher attributes the change in the level of artistic creativity among the experimental group to the clear response of the experimental group to the program, which contributed to an increase in the level of artistic creativity. According to the researcher, it is the kindergarten teacher's desire and motivation to learn. This is consistent with Skinner and Bandura's theory. These results are consistent with the results of developing artistic creativity among kindergarten teachers, as shown in the study (Kabli, 2005), the study (Al-Hisi, 2013), (Mohammed, 2012), and (Ayoub, 2009).These studies showed that collage training increases the artistic and creative skills of the sample members. This is due to several reasons: The program was designed according to the requirements and needs of kindergarten teachers, so that it is compatible with their abilities. According to experts in the field, collage training has important artistic and creative value for the teacher. The researcher, based on her experience and specialization in art education, considers collage to be one of the modern arts used in kindergarten. It is an important field for producing educational paintings for children in a distinctively creative way. The researcher used various materials and educational tools to convey The learner is guided by the research objective. The results also revealed no statistically significant differences between the control group in the pretest (i.e., before and after the program was implemented) and the control group. This is due to the fact that the individuals in the control group were not subjected to the training program for the current research